2011
DOI: 10.1007/s12076-011-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MAUP on spatial econometric models

Abstract: Aggregation effect, Loss in efficiency, MAUP, SARAR models, Scale effect, Spatial econometric, C21, C31, C5,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Moreover, Arbia and Petrarca (2011) present a general framework to investigate the effects of MAUP on spatial econometric models showing how the presence of spatial effects affects the classical results. Arbia and Petrarca (2011) concentrate on the loss in efficiency of the parameters' estimators due to aggregation.…”
Section: Spatial Panel Data Modelsmentioning
confidence: 99%
“…Moreover, Arbia and Petrarca (2011) present a general framework to investigate the effects of MAUP on spatial econometric models showing how the presence of spatial effects affects the classical results. Arbia and Petrarca (2011) concentrate on the loss in efficiency of the parameters' estimators due to aggregation.…”
Section: Spatial Panel Data Modelsmentioning
confidence: 99%
“…7 The effect of the selection of spatial units on analysis is in the statistical literature known as the modifiable areal unit problem (MAUP) (cf. Arbia, 1986;Unwin, 1996), delineated by commuter flows. Using data on job commuters across German districts, Eckey by and large, high-income regions match with high-wage regions.…”
mentioning
confidence: 99%
“…For example, Park & Hewings (2012) revealed that the degree of spatial dependency increases with the use of more disaggregated temporal data. Also, Arbia & Petrarca (2011) deal with the modifiable areal unit problem (MAUP), and showed that the estimated parameters changes with the aggregation of the spatial units. In this paper, since the focus is on the business cycle analysis of the six Great Lake states, and the more disaggregated temporal frequency is thought to best reveal the spatial dependency structure, monthly state level data are used.…”
Section: Notesmentioning
confidence: 99%